Global mapping of attenuation at Ku and Ka bands: statistical and microphysical studies - Mubarak, Khalid, author; Chandrasekar, V., advisor; Lile, Derek, committee member; Bringi, V. N., committee member; Mielke, Paul, committee member (Colorado State University. Libraries, 2003)
The propagation of radio waves for earth-space slant path at C-band and higher frequencies are dominated by precipitation in the atmosphere. At a given frequency, attenuation depends on the length of the radio path, the size distribution and the phase state of the hydrometeor profile. Using the observations from the Tropical Rainfall Measurements Mission (TRMM) spaceborne Ku-band (13.8GHz) radar at Low Earth Orbit of 350km above earth, global attenuation maps are produced at the Ku-band frequency. A simple precipitation microphysical model developed using hydrometeor size distributions and thermodynamic phase state is used to estimate attenuation and reflectivity observations at Ka-band (35GHz) where numerous high bandwidth satellite applications are being planned including the next generation space-based radar for the Global Precipitation Mission (GPM). Differences in the microphysical structure in convective and stratiform precipitation are also incorporated in the model. The results show substantial attenuation variation in a 12-month period at both Ku- and Ka-bands over the various regions of the globe. Including the contrast between land and ocean, the estimates made at Ku- and Ka-band will be useful in the design and development of space systems. The precipitation radar uses surface reference method to estimate the attenuation encountered in the observation of radar reflectivity. The cumulative attenuation (A) estimated from the surface reference method can be distributed along the radar range using a power law relation between the specific attenuation (k) and reflectivity factor (Z) written as, k = αZβ. A commonly used approximation is that 8 is constant and a changes according to the precipitation microphysics. More recently physical interpretation of a has been provided with the normalized drop size distributions. This research describes a procedure to estimate the raindrop size distribution (RSD) parameters from the measured attenuation and reflectivity values obtained from TRMM precipitation radar observations at a global scale. Coincident data collected with ground radar during the TRMM field campaigns have been used to cross-validate the estimates of RSD parameters obtained from TRMM precipitation radar measurements with those obtained from ground polarimetric radar observations. The results of cross-validation show fairly good agreement with the RSD parameters retrieved from TRMM precipitation radar and the ground radar based estimates. The algorithm is also used to generate monthly global maps of RSD parameters. Finally, data from TRMM are used to examine the surface cross section as well as the height of bright band (HBB) over the ocean and land in rain and rain-free regions.
Keywords: electrical engineering